Stability of refrigerated miglustat after preparation in InOrpha® flavored suspending excipient for compounding of oral solutions and suspensions - Riahi S; Ambühl M; Stichler J; Bandilla D (Dove Medical Press, 2015)
Sofyen Riahi, Michael Ambühl, Jürgen Stichler, Dirk Bandilla Actelion Pharmaceuticals Ltd, Allschwil, Switzerland Background: Miglustat (Zavesca®) is an oral treatment for type 1 Gaucher disease and Niemann–Pick disease type C. Patients with Niemann–Pick disease type C often have difficulties swallowing, and miglustat has an unpleasant taste. The stability of miglustat at 2°C–8°C prepared in InOrpha® suspending vehicle, a liquid taste-masking agent, was assessed.Methods: The contents of Zavesca® 100 mg capsules (a powder blend comprising miglustat and several excipients) were transferred into InOrpha®. Although miglustat was soluble in InOrpha® at all concentrations tested, some of the excipients were not. An InOrpha® suspension containing 20 mg/mL miglustat was investigated initially. Subsequently, a pH-adjusted suspension of 20 mg/mL, and non-adjusted 10 and 5 mg/mL suspensions were evaluated. All suspensions were stored under refrigerated conditions. Physicochemical and microbiological challenge testing was performed at 0 hours and after 14 and 28 days. Degradation was assessed by high-performance liquid chromatography, appearance was assessed visually, and pH was recorded. Suspensions were inoculated with seven species of bacteria, yeast, and mold, and growth evaluated using membrane filtration.Results: Miglustat 20 mg/mL suspension changed from yellow (0 hours) to brown (days 14 and 28); pH remained stable at 7.4–7.6. Pure InOrpha® (pH 4.6) remained yellow throughout the study. Pure InOrpha® adjusted to pH 7.5 displayed a brownish discoloration after 9 days. Miglustat 5 and 20 mg/mL suspensions, adjusted to pH 6.5 and 4.4, respectively, remained yellow at days 14 and 28. Miglustat 10 mg/mL suspension (pH 7.3) changed from yellow to brown on day 9. No degradates were detected for any of the concentrations tested. There was no proliferation of microorganisms over the study period; in all cases the level of contamination was clearly reduced.Conclusion: InOrpha® suspensions containing miglustat 5 mg/mL (without pH adjustment) and 20 mg/mL (with pH adjusted to 4.4) display stable physicochemical and microbiological properties over 28 days. Keywords: microbiological challenge, Niemann–Pick disease type C, type 1 Gaucher disease